Determination of ADMET properties of substituted-piperidine-3-carboxamide derivatives with potential use in the treatment of Crohn’s disease - İslamoğlu, F. (International Journal of Biology and Chemistry, 2025)
In this study, ADME studies were carried out on seven different substituted-piperidine-3-carboxamide derivatives compounds, which were considered as drug active ingredients that can be used in the treatment of Chron’s disease with docking studies that were done in our previous studies. In this context, these molecules were examined in terms of physicochemical properties, lipophilicity, water solubility, absorption property, distribution property, metabolism property, toxicity property, environmental toxicity property, tox21 pathway property, and medicinal chemistry property. According to the results obtained, it was concluded that (E)-4-((4-(((4-bromopyridin-1(2H)-yl)methylene)amino)-3-(4-methoxy phenyl)-5-oxo-4,5-dihydro-1H-1,2,4-triazol-1-yl)methyl) piperazine-1-carboxylic acid molecule is the most ideal molecule that can be used in the treatment of Chron’s disease in terms of ADME properties among the molecules studied. Keywords: Crohn’s disease, piperidine-3-carboxamide derivatives, ADME properties, physicochemical properties, toxicity property, medicinal chemistry property